Antioxidant, enzyme-inhibitory and antitumor activity of the wild dietary plant Muscari comosum (L.) Mill. (International Journal of Plant Biology, 2017)
Conventional medicines used to treat obesity and cancer frequently exhibit high side effects, so that researchers are focusing on new therapies and drugs based on natural products. Total extracts from bulbs of Muscari comosum were tested for i) free radical scavenging activity, ii) in vitro enzymatic inhibition of pancreatic α-amylase and lipase, and iii) inhibition of the growth of breast adenocarcinoma cells. Three treatments were considered: bulbs boiled in water for 15 min (traditional cooking method; BB); bulbs steam-cooked for 15 min (alternative cooking method; SB); raw bulbs (RB). The polyphenol content and antioxidant capacity of bulb extracts were related to the inhibition of pancreatic lipase and α-amylase, whose activities have been found to have a half maximal inhibitory concentration (IC50) of 0.28, 2.14 and 3.22 mg/mL for lipase, and 0.16, 0.73 and 0.69 mg/mL for α-amylase in RB, SB and BB, respectively. The analysis on breast adenocarcinoma MCF-7 cells revealed that RB extracts, and in a lesser extent BB, exerted a dose-dependent inhibition on cell proliferation. Considering that the potential of natural products for the treatment of obesity are under exploration, M. comosum could be an excellent plant for the development of future anti-obesity drugs, also able to prevent cancer.